PELECEHAN SEKSUAL DI ANGKUTAN KRL EKONOMI DARI PERSPEKTIF PELAKU - Karliana, Annisa; Prabowo, Hendro (FSTPT Indonesia, 2015)
This paper presents the results of a qualitative research in type of case study about sexual harassment in the kereta KRL Ekonomi (Economics Electric Railway train) based on an actor's perspective. Two students were the subject of research, namely A and B, both were the actor of sexual harassment in the KRL Ekonomi. Both were passenger of Bogor – Depok route of the train. The results showed that A did so by starring up the victim's body, while B did by rubbing his body parts on the victim. In the act, A was not concerned with the situation in the train, while B saw the situation first before doing the action.